Quarter Car Suspension System With One Degree Of Freedom Simulated Using Simulink - Bereteu L. (Annals of West University of Timisoara: Physics, 2012)
Simulate the behavior of a quarter car suspension system with Simulink®. Consider only vertical movement of the car, neglecting roll and pitch. All movements of the car axes are modeled as having equal amplitude. The characteristic equations that describe the behavior of dynamical systems based on FBD (Free Body Diagram) of automotive suspension. We make the simulation model in six steps. In simulation we consider the damping coefficient, c, variable. The rest of parameters are constant (mass, speed and stiffness). The simulation parametrs are defined in Mathlab®. We follow the final signal created on the oscilloscope. At the end of the study, we concluded the effect of damping coefficient changes over the comfort.